Pengaruh Green Accounting terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Subsektor Industri Dasar dan Kimia (2020–2024) - Nuralisa Nuralisa; Anwar Ramli; Anwar Anwar; Nurman Nurman; Abdul Rahman (Pusat Riset dan Inovasi Nasional, 2026)
This research focuses on examining the relationship between environmental accounting practices and firm value creation, considering the role of profitability as an intermediary mechanism. The study was conducted on companies in the basic and chemical industry subsectors listed on the Indonesia Stock Exchange during the 2020–2024 period. Green Accounting in this study is represented through environmental cost disclosure, while firm value is proxied by Price to Book Value (PBV), and profitability is measured by Return on Equity (ROE). The analysis used a panel data regression approach, complemented by a mediation test using the Sobel test. Empirical results indicate that the implementation of Green Accounting has not had a significant impact on profitability or firm value. Conversely, profitability has been shown to have a positive and significant relationship with firm value. Furthermore, the mediation test indicates that profitability plays no role in channeling the influence of Green Accounting on firm value. These findings lead to the interpretation that Green Accounting practices in the studied sectors still reflect regulatory compliance and efforts to gain social legitimacy rather than a strategy to increase short-term economic value.